MAKING TEMPERATURE AND AIR HUMIDITY MONITORING EQUIPMENT IN LECTURE HALLS BASED ON THE INTERNET OF THINGS (IOT) AT BINA BANGSA GETSEMPENA UNIVERSITY BANDA ACEH - Ully Muzakir; Nazuarsya Nazuarsya; Putri Indah Lestari (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Human indifference to the surrounding circumstances sometimes makes their health disturbed. Many factors cause a person to be uncomfortable, even to the point of making their health decline. Factors that can make an uncomfortable person disturbed from a health perspective are temperature and air humidity that are not suitable for the human body. Therefore, a tool is needed that can provide information to users about the temperature and humidity of the air in the lecture hall and where they are located. The tool is made using an arduino IDE and a DHT11 sensor as a sensor used to read air temperature and humidity. Then to transmit the value of the DHT11 sensor, WiFi is used in the circuit. The smartphone will receive information on air temperature and humidity in real time. In the application on the smartphone, in addition to indigo temperature and air humidity, there is also a graph indicator that provides good temperature and air humidity information for human. With this tool, it can make it easier for users to find out information on the temperature and humidity of the air in the room where they are located, such as in a lecture hall